ANALYSIS FACTOR KURS, INFLATION RATE, INTEREST RATE AND BANK CENTRAL SHARIA CERTIFICATE OF SHARIA STOCK INDEKS - Mukhlisul Muzahid; Lukman; Aryati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to determine the effect of the exchange rate, inflation rate, interest rate, and central bank sharia certificate on the sharia stock index. The data used in this study is in the form of panel data using a sample of 50 companies registered on the sharia stock index for 2017-2021. The data analysis technique in this study uses panel data analysis with the fixed effect model. The results showed that simultaneously the exchange rate, inflation rate, interest rate, and the Central Bank's sharia certificate had a significant effect on the sharia stock index. This is based on the results of the F test, namely the calculated F value > F table (47.86140> 2.44) with a prob level (F-Statistic) of 0.000 using an α level of 0.05 or 5%. While partially the exchange rate and inflation rate have no effect on the sharia stock index, but the interest rate and the central bank sharia certificate have a significant effect on the sharia stock index.